If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11z + -3 + -7z = 5 Reorder the terms: -3 + 11z + -7z = 5 Combine like terms: 11z + -7z = 4z -3 + 4z = 5 Solving -3 + 4z = 5 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4z = 5 + 3 Combine like terms: -3 + 3 = 0 0 + 4z = 5 + 3 4z = 5 + 3 Combine like terms: 5 + 3 = 8 4z = 8 Divide each side by '4'. z = 2 Simplifying z = 2
| 35-7b=-7(b-5) | | f(x)=x^3-3x+28 | | -.25w-20=30 | | n-6-7=-4n+8n+23 | | 11x+2=5x+20 | | -12-2r=r-9 | | 9x-11-1=-24+6x | | 9x=150+7x | | 1/x^2+8/x+15=0 | | 3x/x^2-5 | | a/q+b=c | | 3/5(x-5)=x+1 | | Onefourthy-2x=5 | | 2x=10-3x+15 | | 6x+9-x=180 | | 7n+12=8+f/2 | | 3/5(x-12)=x-24 | | 1/10=m/12 | | 13-5r=2r-5(-8-4r) | | 6xy-8x=(6y-8)x | | 46/57.5=360/q | | y^8/25 | | Wsquared+15w=324 | | 0.23+7.1=-0.8 | | 5/u=60/132 | | -v+5+6v=1+5+5v+3 | | x-3+3x/8=-3+11x/8 | | 0.23+7.1=0.8 | | r/9=5/20 | | -5x-2(4-5x)=-10+3x | | y=-13x/6+25/2 | | 12x-(2x+4)+24=5x |